Resilience and Moral Character Among University Students in the Era of Technological Disruption: A Phenomenological Study of BKI Students at UIN Mataram - Fitriana, Herlina; Prayona, Baiq Arwindy; Bafadal, Iqbal (Prodi Pengembangan Masyarakat Islam Fakultas Dakwah dan Ilmu Komunikasi UIN Mataram, 2025)
Based on preliminary research findings, many students feel easily defeated by their circumstances and tend to complain. Additionally, many students experience a degradation in morality when communicating with lecturers. The method used in this study is qualitative with a phenomenological approach, interviewing 20 students from the BKI program. The results show that only 5 out of 20 students are resilient, while the other 15 tend to give up easily and experience stress, with 2 of them even contemplating suicide. Based on the interviews, it was found that each student is capable of both good and bad behaviors, such as stealing, lying, showing a lack of empathy, and being impolite toward elders. Their moral character varies, influenced by personal experiences, trauma, and their environmental conditions.